Zinc oxide nanoparticles synthesized from Aspergillus terreus induces oxidative stress-mediated apoptosis through modulating apoptotic proteins in human cervical cancer HeLa cells. (16th January 2021) - Chen, Hua; Luo, Liping; Fan, Sisi; Xiong, Yuanhuan; Ling, Yan; Peng, Shiwei
Abstract: Objectives: This study was aimed to analyze the cytotoxicity of biogenic zinc oxide nanoparticles (ZnO NPs) in human cervical epithelial cancer HeLa. Methods: The ZnO NPs was synthesized from the culture filtrated of Aspergillus terreus, and examined by UV-spectroscopy, X-ray diffraction (XRD), transmission electron microscope (TEM), energy-dispersive X-ray (EDX) and Fourier transform infrared (FTIR) analysis. The cytotoxicity of synthesized ZnO NPs was analyzed by the MTT assay, and the expression of apoptotic proteins was examined by Western blot analyses. Key findings: The ZnO NPs exhibited concentration-dependent cytotoxicity on HeLa cells and induced the apoptosis as evidenced by reduced superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) levels, and increased reactive oxygen species (ROS) and diminished mitochondrial membrane potential (MMP) was noticed in ZnO NPs treated HeLa cells. Western blot analyses explored that the Bcl-2 expression was significantly downregulated, whereas, the expression of p53, Bax, Caspase-3, Caspase-9 and Cytochrome-c were significantly upregulated in ZnO NPs treated cells. Conclusion: Consequently, the mycosynthesized ZnO NPs induces apoptosis in HeLa cells by persuading oxidative damage and modulating the apoptotic proteins. Therefore, A. terreus synthesized ZnO NPs could be used as an effective chemotherapeutic agent for cervical cancer treatment.